Pemberdayaan Masyarakat dalam Usaha Budidaya Pisang Melalui Pemanfaatan Trichoderma di Desa Klungkung Kecamatan Sukorambi Kabupaten Jember - Fahdia Maulita Yuniar (Fakultas Pertanian)
Empowering communities to tackle Fusarium wilt disease is a major issue that has a big impact on farmers' family economies, often leading to crop failure. This situation needs more attention, so eco-friendly control measures that can deal with Fusarium wilt in banana plants are needed. This study aims to analyze the process of empowering banana farmers in efforts to tackle Fusarium wilt disease in Klungkung Village, Sukorambi District, Jember Regency, focusing on the stages of awareness, capacity building, and empowerment. The method used is qualitative descriptive with a case study design. Informants were chosen purposively, including the head of the farmer group, group members, and agricultural extension workers. Data was collected through in-depth interviews, observation, and documentation, and analyzed using the Miles and Huberman approach through condensation, display, and drawing conclusions. The results show that empowerment has mainly taken place at the awareness and capacity-building stages, where farmers have started to understand the impact of Fusarium, attended training, and practiced biological control methods like using Trichoderma. Meanwhile, the empowerment stage has shown progress among some farmers but is not yet consistent, so independence still needs to be strengthened. The main recommendations of this study are to increase the intensity of continuous mentoring, strengthen the role of group leaders or cadres, and optimize the functions of KWT and farmer groups to expand the adoption of biological technology and improve the sustainability of disease control.
Keywords: Community Empowerment; Banana Commodities; Fusarium Wilt